Well-posedness Techniques in the Qualitative Analysis for a class of Equilibrium problems - Hashoosh, Ayed E.; mohammady, Mohsen Ali; Almusawi, Amneh (Sulaimani Journal for Pure and Applied Sciences, 2017)
The main goal of this paper is to establish some well-posedness results for a nonstandard equilibrium problem (for short ) and for optimization problem involving α-monotone bifunction, whose solution is sought in a subset K of a real reflexive Banach space X. Moreover, we establish some metric characterizations of well-posedness for a nonstandard equilibrium problems and for an optimization problem.
Keywords: Equilibrium problem Wellposed optimizat ion problems bifunction monotone Metric char acterizeations